Simultaneous determination of kaempferol, quercetin, mangiferin, gallic acid, p‐hydroxybenzoic acid and chlorpheniramine maleate in rat plasma after oral administration of Mang‐Guo‐Zhi‐Ke tablets by UHPLC‐MS/MS and its application to pharmacokinetics. (13th December 2017) - Xu, Weijie; Deng, Jiagang; Qian, Yiyun; Hou, Xiao‐Tao; Zhu, Zhenhua; Zhao, Ming; Shang, Erxin; Qian, Dawei; Zeng, Huiting; Pang, Hanqing; Duan, Jinao
Abstract: Mang‐Guo‐Zhi‐Ke tablets (MGZKTs) is an effective Chinese patent medicine. It contains mango leaf extract as the main raw material and the antihistamine drug, chlorpheniramine maleate is included in the formulation. However, its pharmacokinetic effect is rarely reported. A highly sensitive, reliable and rapid high‐throughput method using ultra‐high‐performance liquid chromatography with tandem mass spectrometry (UHPLC‐MS/MS) was used to simultaneously determine kaempferol, quercetin, mangiferin, p ‐hydroxybenzoic acid, gallic acid and chlorpheniramine maleate in rat plasma after oral administration of MGZKTs. The method was successfully developed and fully validated to investigate the pharmacokinetics of MGZKTs. Chloramphenicol and clarithromycin were used as internal standards (IS). A practicable protein precipitation procedure with methanol was adopted for sample preparation. The samples were separated on an Acquity UHPLC Syncronis C18 column (100 × 2.1 mm, 1.7 μm) using 0.1% formic acid–acetonitrile as the mobile phase. The flow rate was set at 0.4 mL/min. The obtained calibration curves were linear in the concentration range of ~1–1000 ng/mL for plasma ( r > 0.99). Method validation results met the criteria reported in the US Food and Drug Administration guidelines. Quercetin, p ‐hydroxybenzoic acid and kaempferol were absorbed rapidly and reached the peak concentration between 0.16 and 0.25 h. This validated that the UHPLC‐MS/MS method was successfully applied to study the pharmacokinetic parameters of the six compounds in rat plasma after oral administration of MGZKTs. This evidence will be useful for the clinical rational use of Mang‐Guo‐Zhi‐Ke tablets.